African commitments for agricultural development goals and milestones for Cote d’Ivoire - Diallo, Souleymane Sadio; Fofana, Ismaël; Diallo, Mariam Amadou (International Food Policy Research Institute, 2020)
The main purpose of this study is to assess the contribution of agricultural investment to the achievement of Côte d'Ivoire's development objectives. More specifically, it aims to analyze the extent to which the implementation of the National Agricultural Investment Programme can contribute to the achievement of the objectives and targets of the Comprehensive Africa Agriculture Development Program (CAADP), the United Nations’ Sustainable Development Goals (SDGs) and the African Union's Agenda 2063. The methodological used combines a computable general equilibrium (CGE) model and a microsimulation model to assess the impact of agricultural investment options on different outcomes related to the different agendas above. The simulation results indicate that the implementation of the NAIP would enable Côte d'Ivoire to make significant progress and achieve some of the CAADP, SDGs and the African union’s 2063 Agenda’s targets. Thus, the country could achieve investment targets by slightly exceeding the 10% share of public expenditure in total government expenditure and a significant increase in private investment in agriculture. This progress in terms of investment could result in an acceleration of agricultural growth so that Côte d'Ivoire's agricultural GDP would increase at a growth rate above the target of 6% per year. It would also make it possible to achieve several SDGs by 2030, as well as certain targets of the African Union's Agenda 2063. However, despite progress in terms of productivity in some segments of the agricultural value chain, the fight against poverty will remain a major challenge that the country will not be able to meet.